LEADERSHIP STYLES AND WORK ENGAGEMENT AN INVESTIGATION INTO EFFECTIVELEADERSHIP PRACTICES - Zakhi Bailatul Nur Avian; Asep Ferry Rachmat; Amra Ulvita Azhiin; Arif Jalaludin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study investigates the impact of different leadership styles on employee work engagement, with a focus on identifying effective leadership practices that foster high levels of engagement. The research examines three primary leadership styles— transformational, transactional, and laissez-faire—and their influence on work engagement dimensions, including vigor, dedication, and absorption. A mixed- methods approach was used, combining quantitative surveys from 450 employees across various industries and qualitative interviews with 25 organizational leaders and HR professionals. The results reveal that transformational leadership is the most effective in driving work engagement, as it encourages employee empowerment, motivation, and personal development. Employees under transformational leaders reported high levels of engagement, particularly in terms of dedication and absorption. In contrast, transactional leadership showed moderate effects, with employees reporting engagement primarily related to performance and target achievement, but lower levels of emotional involvement. Laissez-faire leadership, characterized by minimal involvement and guidance, had the most negative impact on employee engagement, leading to feelings of disconnection, disengagement, and low morale. The study highlights the importance of adopting transformational leadership practices to cultivate an engaged workforce, while suggesting that organizations should limit the use of transactional and laissez-faire leadership approaches. By focusing on leadership development that promotes trust, innovation, and personal growth, organizations can improve work engagement, resulting in enhanced productivity, job satisfaction, and long-term organizational success.